Pengaruh Sumber Asam Basa terhadap Sifat Fisik dalam Formulasi Granul Effervescent : Tinjauan Pustaka - Reza Pratama; Ida Hasanah; Widya Nurasih; Novaliana Devianti Sagita (Bachelor of Pharmacy Study Program, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
Background: Indonesia has abundant natural resources, including types of herbal plants. Herbal plants in Indonesia have various health benefits and have been widely processed in the form of functional drinks. Aim:. To reduce the often undesirable taste and odor characteristics of herbal medicine, it can be further processed into derivative products that taste good and have a longer shelf life. One way is to process it into an effervescent preparation. Method: Searching and collecting journal information is carried out electronically, namely by accessing international and national journal search sites such as online from Pubmed, Google Scholar and Sciencedirect. by using the keywords